Remediation of contaminated sand by Cd ions with variation operation: Batch and flushing column with foam and without foam of SDS surfactant - Bode Haryanto; Rondang Tambun; MZ Siswarni; Vikram Alexander; Tubagus RF Sinuhaji (South African Journal of Chemical Engineering, 2023)
An anionic surfactant, Sodium dodecyl sulfate (SDS), was applied to remove Cd ions as contaminants on the sand surface. The remediation operation approach was used, such as batch, flushing column without foam, and with foam of SDS solution. Increasing the SDS concentration is possible to improve the removal ability of Cd ions from the sand surface. For batch, the operation performs the higher removal ability by increasing the shaking rotation per minute (rpm). Fluctuation of the percentage removal efficiency (% RE) was shown by using a flushing column without foam at each flow rate variation. The channeling effect during flushing in the column was proved to be the cause of fluctuation in the removal efficiency. Flushing with foam is possible to increase the removal efficiency from 10% by batch and flushing without foam to about 70% with foam. The increasing flow rate of surfactant SDS solution is possible to increase the removal efficiency and flow to the intra-particle area of sand and then decrease the channeling effect. Flushing in column approach with foam by anionic surfactant SDS shows the higher ability and more efficiency in the removal of Cd ions on the sand surface.